Output feedback nonlinear control of three-phase grid-connected PV generator - Abdelhafid Yahya; Hassan El Fadil; Mustapha Oulcaid (Institute of Advanced Engineering and Science, 2019)
This paper addresses the problem of controlling three-phase grid connected PV system involving a PV arrays, a voltage source inverter, a grid filter and an electric grid. This paper presents three main control objectives: i) ensuring the Maximum power point tracking (MPPT) in the side of PV panels, ii) guaranteeing a power factor unit in the side of the grid, iii) and ensuring the asymptotic stability of the closed loop system. Interestingly, the present study features the achievement of the above energetic goal without resorting to sensors of currents of the grid. To this end, an output-feedback control strategy combining a state observer and a nonlinear control laws is developed. The proposed output-feedback control strategy is backed by a formal analysis showing that all control objectives are actually achieved